The school food environment and adolescent obesity: qualitative insights from high school principals and food service personnel - Ellerbeck Edward F; Daley Christine; Snow Patricia; Befort Christie A; Nollen Nicole L; Ahluwalia Jasjit S (BMC, 2007)
Abstract Objectives To examine high school personnel's perceptions of the school environment, its impact on obesity, and the potential impact of legislation regulating schools' food/beverage offerings. Methods Semi-structured interviews were conducted with the principal (n = 8) and dietitian/food service manager (n = 7) at 8 schools (4 rural, 4 suburban) participating in a larger study examining the relationship between the school environment and adolescent health behavior patterns. Results Principal themes included: 1) Obesity is a problem in general, but not at their school, 2) Schools have been unfairly targeted above more salient factors (e.g., community and home environment), 3) Attempts at change should start before high school, 4) Student health is one priority area among multiple competing demands; academic achievement is the top priority, 5) Legislation should be informed by educators and better incorporate the school's perspective. Food service themes included: 1) Obesity is not a problem at their school; school food service is not the cause, 2) Food offerings are based largely on the importance of preparing students for the real world by providing choice and the need to maintain high participation rates; both healthy and unhealthy options are available, 3) A la carte keeps lunch participation high and prices low but should be used as a supplement, not a replacement, to the main meal, 4) Vending provides school's additional revenue; vending is not part of food service and is appropriate if it does not interfere with the lunch program. Conclusion Discrepancies exist between government/public health officials and school personnel that may inhibit collaborative efforts to address obesity through modifications to the school environment. Future policy initiatives may be enhanced by seeking the input of school personnel, providing recommendations firmly grounded in evidence-based practice, framing initiatives in terms of their potential impact on the issues of most concern to schools (e.g., academic achievement, finances/revenue), and minimizing barriers by providing schools adequate resources to carry out and evaluate the effectiveness of their efforts.